1958
DOI: 10.1111/j.1151-2916.1958.tb13521.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Carbonate Decomposition in Carbon Dioxide Atmosphere

Abstract: Calcite crystal fragments of known surface area were decomposed in controlled carbon dioxide atmospheres. The decomposing sample was weighed continuously on an automatically recording themobdance and a rate of weight loss per unit area was obtained. A rate expression involving actual and equilibrium COr pressures and the decomposition rate in pure nitrogen was derived. The mechanism of the decomposition is pictured as being a two-stage phenomenon. Initially the C 0 2 leaves the CaC03 cell and the residue of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

1960
1960
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 6 publications
7
89
0
Order By: Relevance
“…According to our results, the ratio between the carbonation rates of the fast reaction regime to those of the slow one is about two orders. This is in accordance with the results of both Hyatt et al (1958) and Barker (1973).…”
Section: Resultssupporting
confidence: 82%
“…According to our results, the ratio between the carbonation rates of the fast reaction regime to those of the slow one is about two orders. This is in accordance with the results of both Hyatt et al (1958) and Barker (1973).…”
Section: Resultssupporting
confidence: 82%
“…It is clear that the reaction at the interface CaCO 3 -CaO is complex and not fully understood. Several workers have suggested that the non-linear dependence found for the effect of CO 2 on the calcination rate could be due to the existence of a sorption process at the calcination surface (Hyatt, Cutler & Wadsworth, 1958;Wang & Thomson, 1995;Khinast et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The calcination rate increases monotonically with decreasing absolute pressure because of reduced intraparticle mass transfer resistances and increased driving force (Hyatt, Cutler, & Wadsworth, 1958;Sakadjian et al, 2007). Increased pressure results in an increase in the internal mass transfer resistances in the sorbent porous network.…”
Section: Calcination Kineticsmentioning
confidence: 98%